PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBASIS INQUIRY TERHADAP KETERAMPILAN PROSES SAINS SISWA KELAS XI SMA UNGGUL N 4 PALEMBANG - Puji Setya Ningsih, Agus; Andinasari, Andinasari; Sugiarti, Sugiarti (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
The problem in this research was the less learning to train students science process skills. This study aimed at determining the positive influence of contextual teaching and learning approach based on inquiry to the skills of science process students of grade XI SMA Unggul N 4 Palembang. The research method used was quasi experimental design. Population in this research were all class XI MIPA SMA Unggul N 4 Palembang. Technique of collecting data was using observation. Based on the results obtained average score of the overall skills of the students science process of 2.53 with high category (in the range 1-4). So it can be concluded that the contextual teaching and learning approach based on inquiry have a positive effect on students science process skill.